Laboratory Investigation on Discharge Coefficient of Trapezoidal Piano Key Side Weirs - Minasadat Seyedjavad; Seyed Taghi Omid Naeeni; Mojtaba Saneie (Salehan Institute of Higher Education, 2019)
A spillway is a hydraulic structure used to provide the controlled release of surplus waters and floods from a dam into a downstream area. A side weir is a multipurpose hydraulic structure which is constructed in water conveyance systems with a height lower than that of the canal wall. When the water surface level goes up, the side weir regulates the discharge and controls the water surface in the main canal. Besides, the side weir controls and diverts floods in dam reservoirs, diverts the flow and protects the structure against the river inundations. In this research, a laboratory investigation is performed with 16 Type-A piano key weirs and three different pier heights of 10, 15 and 20cm. These weirs are studied for two cases of 1 and 2. The results show that the weirs with 15cm and 20cm heights in both cases 1 and 2 have the highest discharge coefficient in dimensionless ratios of 0.2> H/P> 0.4 and H/P>0.5 respectively. Having reviewed previous studies, it could be concluded that the trapezoidal piano key side weir is capable of releasing a flow 1.2 times more than that of the linear trapezoidal labyrinth weir with 12 degrees angle and 1.87 times more than the one with 6 degrees angle, and 1.5 times more than that of the triangular labyrinth weir.